The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1258/ebm.2012.012255
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil-induced hypothyroidism during lactation alters leucine and mannose metabolism in rat cerebellar slices

Abstract: Thyroid hormone deficiency during perinatal development results in significant alterations in neurological functions. The relationship between such events and brain metabolism is not completely understood. The aim of this study was to investigate the effects of hypothyroidism on leucine, mannose, glucose and lactate metabolism in rat cerebellar slices. Experimental hypothyroidism was induced by exposing mothers and pups to propylthiouracil (PTU) until weaning - postnatal day 21. Metabolic analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…In addition, some studies found that the reduction in PRL levels caused by PTU-induced hypothyroidism may reduce milk production of lactating mothers, which may cause growth retardation in the pups (Tamásy et al 1984, Hapon et al 2007. Some studies have found that after weaning, the bodyweight of hypothyroid rats that continued to receive PTU did not change between 28 and 40 days (Dussault & Walker 1978, Dijkstra et al 1996, Mendis-Handagama & Ariyaratne 2004, whereas those that no longer received PTU gradually increased weight, and then returned to normal weight after 100 days (Jena et al 2012, Müller et al 2013, Rijntjes et al 2017. Therefore, we suggest that although there was a confounding effect of growth delay before weaning, the growth retardation of neonatal hypothyroidism was mainly due to the decrease in serum GH levels caused by the decreased number of pituitary eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies found that the reduction in PRL levels caused by PTU-induced hypothyroidism may reduce milk production of lactating mothers, which may cause growth retardation in the pups (Tamásy et al 1984, Hapon et al 2007. Some studies have found that after weaning, the bodyweight of hypothyroid rats that continued to receive PTU did not change between 28 and 40 days (Dussault & Walker 1978, Dijkstra et al 1996, Mendis-Handagama & Ariyaratne 2004, whereas those that no longer received PTU gradually increased weight, and then returned to normal weight after 100 days (Jena et al 2012, Müller et al 2013, Rijntjes et al 2017. Therefore, we suggest that although there was a confounding effect of growth delay before weaning, the growth retardation of neonatal hypothyroidism was mainly due to the decrease in serum GH levels caused by the decreased number of pituitary eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperthyroid groups were given (0.0012% w/v) L-Thyroxine in drinking water for 40 days [22] and the hypothyroid groups were given Propylthiouracil (PTU) (0.05% w/v) [23].…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, the content of the central well was transferred to vials and assayed for radioactivity in a liquid scintillation counter. All results were calculated based on the initial radioactivity in the incubation medium and expressed in pmol/mg of tissue (Müller et al, 2013). …”
Section: Methodsmentioning
confidence: 99%